Coronary artery calcium on lung cancer radiation planning CT aids cardiovascular risk assessment - Matthew Lui; Noah Kim; Raja Zaghlol; Pouya Joolharzadeh; Elena Deych; Clifford Robinson; Shahed Badiyan; Pamela K. Woodard; Joshua D. Mitchell (Cardio-Oncology)
Abstract Background Patients with non-small cell lung cancer (NSCLC) undergoing thoracic radiation are at high cardiovascular risk. Semiquantitative assessment of coronary artery calcification (CAC) on baseline planning non-gated chest computed tomography (CT) scans may help further risk stratify patients. Objectives This study aimed to characterize the association between CAC and major adverse cardiovascular events (MACE; myocardial infarction or stroke) and assess the utility of semiquantitative assessment of CAC. Methods Patients with NSCLC with non-contrast planning chest CT scans were evaluated for CAC. Planning scans were visually graded using the CAC-DRS method, stratifying patients into no, mild, moderate, and severe CAC groups. Demographics, comorbidities, and radiation treatment characteristics were gathered, and CAC groups were assessed for the incidence of MACE after initiation of radiation therapy. Results Out of 137 patients, 39 patients had no CAC, and 98 patients had any CAC (38 with mild CAC, 34 with moderate CAC, and 26 with severe CAC). There was 1 MACE event in the no CAC group and 11 in patients with any CAC. The presence of CAC was associated with increased MACE compared to no CAC (p = 0.034). Semiquantitative CAC analysis correlated with formal CAC scoring. Conclusion There is a significantly lower incidence of MACE in patients with no CAC on planning CT compared to patients with higher burdens of CAC. CAC burden is an important risk factor for adverse cardiovascular events in patients with NSCLC undergoing thoracic radiation. Semiquantitative CAC scoring may be a useful proxy when formal CAC scoring is unavailable.